Pengaruh Kompetensi Kepribadian Guru PAK Terhadap Perilaku Siswa SMP - Sahat Bintang Parasian (PT. ALHAFI BERKAH INDONESIA, 2023)
This research aims to determine the positive and significant influence between the Personality Competencies of Religious Education Teachers on the Behavior of Class VIII Students at Karya Murni Sidihoni Private Middle School, Ronggur Nihuta District, Samosir Regency, Academic Year 2023/2024. The method used in this research is quantitative descriptive inferential, with a population of 103 people and a research sample of 36 people, which is 35% of the total population. Data was collected using a closed questionnaire with 32 items compiled by the author based on variable indicators according to expert theory. The instrument was tested on 33 students who were not research respondents, and its validity and reliability were tested. The results of data analysis show that the results of the simple regression equation are Ŷ = 13.08+0.74X. The results of the t test show that the value of tcount>ttable is 2.705>2.042. Next, data analysis for hypothesis testing using the f test obtained Fcount > Ftable, namely 7.31 > 2.23, so it can be concluded that the hypothesis is accepted and based on the results of the coefficient of determination, the magnitude of the influence of the Personality Competence of Religious Education Teachers on the Behavior of Class VIII Students at Karya Murni Sidihoni Private Middle School, District Ronggur Nihuta Samosir Regency for the 2023/2024 Academic Year is 17.7% and another 82.3% is obtained from other factors not examined in this research.